Comportamento higiênico como resposta ao ácaro varroa destructor em abelhas africanizadas (apis mellifera) no semiárido brasileiro - Silva, Leandro Alves da (Universidade Federal Rural do Semi-Árido, 2021)
The health of bees is a topic discussed worldwide, as it is a critical point in the production chain and of fundamental importance for the maintenance of colonies and beekeeping production. The Varroa destructor mite is considered one of the most lethal pests of the bees today and alternative mechanisms for controlling this parasite, without the use of chemical treatments have been studied. Even present in all Brazilian states, V. destructor has not caused the same harmful effects as seen in other countries due to the tolerance of the Africanized bee, the life cycle of the bees, the hygienic behavior sensitive to the mite, the grooming, climate among other factors. Hygienic behavior is considered one of the main defense mechanisms for population control of V. destructor, and the selection of hygienic colonies has been carried out with this objective in mind. With that, in the present work we tried to evaluate the hygienic behavior as a response to this parasite in Africanized bees in the Brazilian semiarid region and, for that, we subdivided the work in 4 stages, here called chapters. In chapter 1 a theoretical fundamentation on the subject was made, in chapter 2 a comparative study of two methods to evaluation of hygienic behavior was carried out, the method of freezing in brood the freezer (FM) and the pin-killing brood method (PM) of the brood with a entomological pin, in order to measure the efficiency of these methods in the ability to remove the brood artificially killed by bees, in 24 and 48 hours after applying them, and based on these results, adopt the best method in the other experiments. A completely randomized design was used, with 4 replications, 17 colonies and 2 treatments. Data collection for this experiment took place between October and December 2019. In chapter 3, the hygienic behavior sensitive to V. destructor (VSH) was evaluated at different phenotypic levels of the general hygienic behavior in Africanized bees (A. mellifera) and its relationship with the rate of infestation in adult bees and brood, moreover, the rate of infestation was correlated with the area of brood operculated. Three groups were formed regarding the expression of hygienic behavior: low (HB<60%), intermediate (60≤HB<80%) and high (HB≥80%). In each group, the VSH, the rate of infestation in broo and in adult bees were evaluated. The capped brood area and climatic variables were collected. Data collection for this experiment took place between June and November 2020. In chapter 4, the infestation rate of V. destructor in adult bees was evaluated from January to December 2020, in hygienic and non-hygienic colonies. Approximately 300 adult bees were collected monthly from each of the 37 colonies and monthly climatic data were also collected to assess its influence on the infestation curve. There was no statistical difference between the methods, both were efficient in the assessment of hygienic behavior both in 24 hours (FM and PM = 66±14) and in 48 hours (FM = 91±9 and PM = 89±11). The freezing method showed a higher rate of capped (FM=33; PM=18) and scored (FM=29.5; PM=21.5) cells and a lower rate of partially removed offspring (FM=21; PM= 30). In Spearman's correlation analysis, no significant correlation was found between HB and VSH (rs = 0.0361, p = 0.7089). Similarly, there was no significant correlation between HB and V. destructor infestation rate both in adult bees (rs = 0.0203, p = 0.8344) and in offspring (rs = - 0.0126, p = 0, 8967). There was a positive correlation between mite infestation in adult bees and mite infestation in offspring (rs = 0.7027, p < 0.0001), however, there was no correlation between VSH and infestation in adult bees (rs = 0, 0873, p = 0.3668) and offspring (rs = 0.0174, p = 0.8577). The results of the analysis showed a negative correlation between brood area and mite infestation in adult bees (rs = -0.5298, p< 0.0001), as well as between mite infestation in brood (rs = -0,6427, P<0.0001). There was a positive correlation between air temperature and mite infestation in adult bees (rs =0.3867, p < 0.0001) and offspring (rs = 0.8071, p < 0.0001). There was a negative correlation between air relative humidity and infestation in adult bees (rs = - 0.5041, p < 0.0001) and offspring (rs = - 0.7324, p = 0.0300), similarly, there was a correlation negative rainfall with infestation in adult bees (rs = - 0.1720, p = 0.0139) and offspring (rs = - 0.3312, p = 0.0004). The average monthly infestation can be considered low, considering that it remained below 10%, with the exception of November, which reached 12.19% ± 6.45, however, there was variation in the infestation between colonies, reaching 42%. There was no statistical difference in the infestation rate between the phenotypic groups (P>0.05). It was observed that the mite infestation associated with the climatic variables influenced the swarming of 32% of the colonies (TºC= 0.3522; UR= -0.40398; PPmm= -0.3981). Hygienic behavior can be assessed by both methods in 24 hours, without the need to assess within 48 hours, however, considering practicality and accessibility, the drilling method is more viable and can be easily applied both in the field and in the laboratory. The hygienic behavior sensitive to V. destructor did not differ between the 3 phenotypic groups. The infestation rate was directly influenced by the brood area. And the mite infestation combined with environmental conditions in the off-season favored colony swarming in the most critical months. There was no significant correlation between the hygienic behavior and the monthly infestation of this parasite, showing that the tolerance of Africanized bees is the result of several factors and not just the hygienic behavior. Even so, the results found reinforce the line of thought that in Brazil there is no need to apply acaricides to control V. destructor
Keywords: Acaricidas; CCD; Sanidade das abelhas; Varroatose; VSH; Acaricides; CCD; Health of the bees; Varroatosis; VSH; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL